Synthesis and biological evaluation of novel marine-derived indole-based 1, 2, 4-oxadiazoles derivatives as multifunctional neuroprotective agents. Issue 2 (15th January 2015) - Jiang, Cheng-Shi; Fu, Yan; Zhang, Li; Gong, Jing-Xu; Wang, Zhen-Zhong; Xiao, Wei; Zhang, Hai-Yan; Guo, Yue-Wei
Graphical abstract: Abstract: Phidianidines (1 ), isolated from the marine opisthobranch mollusk Phidiana militaris, present the first example of natural products possessing an 1, 2, 4-oxadiazole ring system and show various bioactivities. However, the structure–activity relationship study related to1 has not been reported yet. As our ongoing effect toward marine-derived potential neuroprotective agents, a series of phidianidine-based derivatives have been synthesized and evaluated for neuroprotective effects against amyloid-β25–35 (Aβ25–35 )-, hydrogenperoxide (H2 O2 )-, and oxygen–glucose deprivation (OGD)-induced neurotoxicity in SH-SY5Y cells. The bioassay results indicated that some of analogs, especially2q and2r, exhibited good in vitro neuroprotective effects in the above three screening models. The preliminary SAR study indicated that substituent groups introduced to the benzene ring play a crucial role in their bioactivity. In particular, the linear alkoxy group at 4-position favors the neuroprotective activity, while a bulky group could lead the activity decrease or loss. These findings could provide an alternative strategy for the development of novel indole-based 1, 2, 4-oxadiazole derivatives for the treatment of Alzheimer's disease.